EcoHealth approach to control of zoonotic emerging infectious diseases in Southeast Asia: Sharing the experiences - Gilbert, Jeffrey (2013)
The International Livestock Research Institute was established in 1994 through a merger of two livestock research centres belonging the Consultative Group on International Agriculture Research, leading to an expanded mandate. ILRI’s predecessors started out with a geographical focus on East Africa but expanded to other regions: including Southeast Asia.